Position sensor for active magnetic bearing with commercial linear optical encoders - Tantau, Mathias; Morantz, Paul; Shore, Paul (Elsevier, 2021)
Active magnetic bearings are used in a number of applications but their disadvantage is the high asynchronous error due to sensor noise amplification. In this paper a new radial position sensor for active magnetic bearings (AMB) based on linear optical encoders is presented. A commercial encoder scanning head faces a round scale with concentric, coplanar lines on its face. Because such a scale is not readily available, it is made by high precision micro machining and different options are compared. In experiments a measurement noise of 3.5 nm at 10 kHz bandwidth is achieved. In addition, a magnetic bearing is built to demonstrate the sensor in closed-loop.
Keywords: Magnetic bearing; Encoder; Micro machining